The Challenge of 3D Bioprinting of Composite Natural Polymers PLA/Bioglass: Trends and Benefits in Cleft Palate Surgery - Damien Brézulier (MDPI AG, 2021)
Cleft lip and palate is the fourth most common congenital malformation. Its prevalence is about 1 in 750 to 1 in 2000 live births. The consequences of this malformation are major: maxillary growth deficit, unaesthetic appearance, phonation disorders, difficulty in eating, and psycho-social disorders. Cleft palate repair establishes the division between the oral and nasal cavities. The alveolar bone graft is a key step. Different sites of autogenous bone harvesting are used, the most common being the iliac crest. Nevertheless, the large number of complications associated with harvesting has led to the use of substitute biomaterials. Bioactive glasses, discovered in 1969, are a group of synthetic silica-based materials with bone-bonding properties. Although 45S5 granular composition is commonly used in bone surgery to repair critical defects, it is only rarely used in the repair of cleft palates because this galenic form is only moderately adapted. However, advances in bone tissue engineering allow the shaping of three-dimensional scaffolds, which support colonization by host cells. Recent advances in computer-aided design/computer-aided manufacturing (CAD/CAM) have even led to the 3D printing of scaffolds combining 45S5 bioglass with a natural and biocompatible poly-lactic acid matrix. The shape of the parts is customized and adapted to the particular shape of the critical bone defects. The objective of this literature review is to highlight the particularities of alveolar defects subsequent to facial clefts, then to detail the characteristics of the materials and technologies used to elaborate 3D matrices by bioprinting. Finally, we will explore research directions regarding their use in reconstructive surgery of cleft palates.